Efficient Total Chemical Synthesis of 13C=18O Isotopomers of Human Insulin for Isotope‐Edited FTIR. (16th February 2016) - Dhayalan, Balamurugan; Fitzpatrick, Ann; Mandal, Kalyaneswar; Whittaker, Jonathan; Weiss, Michael A.; Tokmakoff, Andrei; Kent, Stephen B. H.
Abstract: Isotope‐edited two‐dimensional Fourier transform infrared spectroscopy (2 D FTIR) can potentially provide a unique probe of protein structure and dynamics. However, general methods for the site‐specific incorporation of stable 13 C= 18 O labels into the polypeptide backbone of the protein molecule have not yet been established. Here we describe, as a prototype for the incorporation of specific arrays of isotope labels, the total chemical synthesis—via a key ester insulin intermediate—of 97 % enriched [(1‐ 13 C= 18 O)Phe B24 ] human insulin: stable‐isotope labeled at a single backbone amide carbonyl. The amino acid sequence as well as the positions of the disulfide bonds and the correctly folded structure were unambiguously confirmed by the X‐ray crystal structure of the synthetic protein molecule. In vitro assays of the isotope labeled [(1‐ 13 C= 18 O)Phe B24 ] human insulin showed that it had full insulin receptor binding activity. Linear and 2 D IR spectra revealed a distinct red‐shifted amide I carbonyl band peak at 1595 cm −1 resulting from the (1‐ 13 C= 18 O)Phe B24 backbone label. This work illustrates the utility of chemical synthesis to enable the application of advanced physical methods for the elucidation of the molecular basis of protein function. Abstract : Just one carbonyl, please : Human insulin was specifically labeled at the (1‐ 13 C= 18 O)Phe B24 backbone carbonyl by using total chemical synthesis via a key ester insulin intermediate. The synthetic protein retained full insulin‐receptor binding activity. Linear and 2 D IR spectra of isotope‐labeled human insulin confirmed the presence of the (1‐ 13 C= 18 O)Phe B24 label.